Relational Mindfulness for Coaches : Enhancing Presence, Awareness, Wisdom, Compassion and Courageous Collaboration - Donaldson-Feilder, Emma; Hall, Liz, 1964- (Routledge, 2025)
The quality of coaches' presence and awareness is key to the quality and success of their coaching relationships and interventions. Relational Mindfulness for Coaches supports coaches to co-create compassionate, psychologically safe yet courageous coaching spaces, generating profound insight, wisdom, and understanding in the client. At the book's heart are powerful practices to expand mindful presence from the individual to the relational, bringing present-moment, non-judgemental awareness to self, others, and the relationship, whilst speaking and listening. The book provides understanding of Relational Mindfulness's (RM's) foundations in mindfulness, compassion, and Insight Dialogue. Drawing on their and other experienced coaches' experiences, the authors illustrate the benefits of engaging in RM practices and provide easy-to-follow guidance for bringing RM into coaching. They also situate RM in the wider field of theory and practice, including neuroscience, and explore RM in relation to a host of other coaching models. In these challenging times of polarisation and conflict, the climate emergency, and a crisis in mental health, this inspiring book addresses the urgent need to create transformational dialogue and interrelatedness in coaching and beyond. This pioneering book will be essential reading for coaches, coaching supervisors, coaching psychologists, coaching academics, leaders, and other helping professionals.